The role of homocysteine levels as a risk factor of ischemic stroke events: a systematic review and meta-analysis - Pinzon, Rizaldy Taslim; Wijaya, Vincent Ongko; Veronica, Vanessa (Frontiers in Neurology, 2023)
Introduction Among numerous risk factors, homocysteine (Hcy) has been linked to cerebral infarction; however, results have been inconsistent. This review aimed to conduct a meta-analysis of published studies to investigate the relationship between plasma Hcy levels and the risk of ischemic stroke. Methods A systematic literature search was conducted until November 2022 to obtain articles reporting Hcy levels in ischemic stroke patients. Review Manager software was used to perform all statistical analyses (version 5.3). Results Initial investigation yielded 283 articles. The final evaluation included 21 articles, including two prospective studies, one retrospective cohort, and 18 case–control studies. These studies included 9888 participants, of which 5031 were admitted patients with ischemic stroke. An integrated analysis revealed that ischemic stroke patients had significantly higher levels of Hcy than controls (mean difference (MD) = +3.70, 95% confidence interval (CI) = 2.42–5.81, p < 0.001). Conclusion This meta-analysis and systematic review indicate that ischemic stroke patients have significantly higher homocysteine levels than controls. Detecting hyperhomocysteinemia and reducing homocysteine levels should be explored among individuals at increased risk for ischemic stroke.